(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Investigating the relationship between sleep quality and signs of depression in the 3-month postpartum period in pregnant women infected with COVID-19. Subject and method: A cross-sectional study was conducted on 223 women infected with COVID-19 giving birth at Hanoi Obstetrics & Gynecology in the period from January 2022 to April 2022. Turkish postpartum sleep quality scale and the Edinburgh Postpartum Depression Questionnaire were used to assess sleep quality and identify the presence of signs of depression in postpartum women. Logistic regression was used to examine the association between sleep quality and signs of postpartum depression. Results: Scores assessing fear of COVID-19 and assessing postpartum social support were associated with signs of postpartum depression. Multivariable regression models showed that the risk of having signs of postpartum depression in women with poor sleep quality was 1.09 times higher than in those with no signs of the disease (p < 0.001). Conclusion: Our study found a relationship between sleep quality and signs of depression in pregnant women in the first 3 months after giving birth.